CORRUPTION OF SOCIETY, CORRUPTION OF THE INDIVIDUAL - Khayrullo Gaibullaevich Azimov (Scholar Express Journals, 2025)
The topic of corruption is taken seriously today as an evil and a disaster. It is quite difficult to determine whether the level of corruption has increased recently, since it is difficult to find any unambiguous measurement for it, but it is possible It's fair to say that public interest in it has grown.
Keywords: possible; corruption; disaster